Cytological Analysis of Body Fluids and Comparison of Precision in Diagnosis Between Conventional Smear and Cell Block Along with Clinical Correlation - Honnappa, Sridhar; S, Ganraj Bhat; B, Prasanna Shetty (Annals of Pathology and Laboratory Medicine, 2019)
Background: The cytological analysis of serous effusions helps in diagnostic, therapeutic and prognostic implications, especially in malignant effusions.This study determines the comparison of precision in cytological analysis between conventional smear and cell block in body fluids with clinical correlation. The study was conducted in M S Ramaiah medical college over a period of 2 years (2016-2018) in the department of pathology on total of 100 fluid cytology samples. Methods and Material: Conventional smears and cell block for the same fluid was performed and cytological analysis done. The cytological data was analyzed for significance in correlation between smear and cell block.The results were tabulated and analyzed using SPSS version 15.0 Results: Cell block was diagnostically superior in 53.11% of cases as compared to conventional smear which was 18.22%. However conventional smear was diagnostically inadequate in 33.98% of cases. Conclusions: Cell block preparations can be combined with conventional smears wherever possible to improve diagnostic accuracy.